Quantitative Assessment of Visceral Obesity and Postoperative Colon Cancer Outcomes - Ozoya, Oluwatobi O.; Siegel, Erin M.; Srikumar, Thejal; Bloomer, Amanda M.; DeRenzis, Amanda; Shibata, David (Journal of gastrointestinal surgery, 2017)
Background Quantitative computed tomography (CT) assessment of visceral adiposity may be superior to body mass index (BMI) as a predictor of surgical morbidity. We sought to examine the association of CT measures of obesity and BMI with short-term postoperative outcomes in colon cancer patients. Methods In this retrospective study, 110 patients treated with colectomy for stage I–III colon cancer were classified as obese or non-obese by preoperative CT-based measures of adiposity or BMI [obese: BMI ≥ 30 kg/m 2 , visceral fat area (VFA) to subcutaneous fat area ratio ( V / S ) ≥0.4, and VFA > 100 cm 2 ]. Postoperative morbidity and mortality rates were compared. Results Obese patients, by V / S and VFA but not BMI, were more likely to be male and have preexisting hypertension and diabetes. The overall complication rate was 25.5%, and there were no mortalities. Obese patients by VFA (with a trend for V / S but not BMI) were more likely to develop postoperative complications as compared to patients classified as non-obese: VFA (30.5 vs.10.7%, p = 0.03), V / S (29.2 vs. 9.5%, p = 0.05), and BMI (32.4 vs. 21.9%, p = 0.23). Conclusions Elevated visceral obesity quantified by CT is associated with the presence of key metabolic comorbidities and increased postoperative morbidity and may be superior to BMI for risk stratification.